Differences in the binding of quinine and quinidine to plasma proteins. - Mihaly, G W (1987)
1. Little is known about the comparative plasma protein binding of the antimalarial agents quinine (QN) and its isomer quinidine (QD). We have examined the in vitro binding of QN and QD to albumin, alpha 1-acid glycoprotein, normal human plasma, and maternal and foetal umbilical cord plasma. 2. QN was more avidly bound than QD, and binding of both drugs was substantially higher to alpha 1-acid glycoprotein than to albumin, indicating that alpha 1-acid glycoprotein is the more important binding protein. 3. Protein and drug concentration dependent binding was evident for both QN and QD. The unbound fraction of both drugs fell with increasing albumin (10 to 60 g l-1) and alpha 1-acid glycoprotein (0.5 to 2.0 g l-1) concentration, and there was a marked increase in unbound fraction of QN (6 to 19%) and QD (13 to 36%) in human plasma when drug concentrations were increased over the antimalarial therapeutic range (0.5 to 10 mg l-1). 4. In human volunteer plasma, the unbound fractions of QN and QD were 7.5 +/- 2.2% and 12.3 +/- 2.3% respectively, whilst the unbound fractions for both drugs were significantly higher in maternal plasma (QN = 13.0 +/- 5.4%, QD = 18.3 +/- 2.5%) and significantly higher still in foetal umbilical cord plasma (QN = 25.7 +/- 10%, QD = 35 +/- 5.3%).